Misfortunes and Shipwrecks in the Seas of the Indies, Islands, and Mainland of the Ocean Sea (1513-1548) : Book Fifty of the General and Natural History of the Indies - Fernández de Oviedo y Valdes, Gonzalo, 1478-1557 (Book collections on Project MUSE., 2011)
These tales of seafaring and shipwrecks have been translated into English from Oviedo's 16th-century reports on the perils and disasters experienced by travellers to and from the New World. These narratives contain important information about colonial navigation, meteorology, geography, shipping, trade routes, and sociology.